1991
DOI: 10.1128/jb.173.19.6153-6158.1991
|View full text |Cite
|
Sign up to set email alerts
|

Detection of elastase production in Escherichia coli with the elastase structural gene from several non-elastase-producing strains of Pseudomonas aeruginosa

Abstract: The elastase structural gene from Pseudomonas aeruginosa IFO 3455 has been cloned and sequenced. Using this gene as a probe, we cloned the DNA fragments (pEL3080R, pEL10, and pEL103R) of the elastase gene from non-elastase-producing strains (P. aeruginosa IFO 3080, N-10, and PA103 respectively). These three Pseudomonas strains showed no detectable levels of elastase antigenicity by Western blotting (immunoblotting) or by elastase activity. When elastase structural genes about 8 kb in length were cloned into pU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…1 ) contained 64.2% G + C base pairs, which was found to be similar (67.2%) to the genomic DNA of P. aeruginosa [Palleroni, 1984]. The nucleotide sequence of P. aeruginosa PseA genomic DNA exhibited more than 95% homology with the las B gene of P. aeruginosa PST-01 [Ogino et al, 2000], PAO1 [Bever and Iglewski, 1988], IFO 3455 [Fukushima et al, 1989], IFO 3080, N-10, PA103 [Tanaka et al, 1991] and PA14 (GenBank accession No. NZ_AABQ07000001).…”
Section: Analysis Of the Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…1 ) contained 64.2% G + C base pairs, which was found to be similar (67.2%) to the genomic DNA of P. aeruginosa [Palleroni, 1984]. The nucleotide sequence of P. aeruginosa PseA genomic DNA exhibited more than 95% homology with the las B gene of P. aeruginosa PST-01 [Ogino et al, 2000], PAO1 [Bever and Iglewski, 1988], IFO 3455 [Fukushima et al, 1989], IFO 3080, N-10, PA103 [Tanaka et al, 1991] and PA14 (GenBank accession No. NZ_AABQ07000001).…”
Section: Analysis Of the Sequencementioning
confidence: 99%
“…A search of databases by the BLASTP revealed that the P. aeruginosa PseA protease was most similar in sequence to the zinc metalloprotease (elastase) secreted from various P. aeruginosa strains as PST-01 [Ogino et al, 2000], PA14 and then with that of PA103, IFO 3455 and N-10 [Tanaka et al, 1991].…”
Section: Phylogenetic Analysis Of the Psea Proteasementioning
confidence: 99%
“…Elastase production and processing are facilitated by a growth medium containing both zinc and calcium ions (22). On the basis of the inferred amino acid sequence (1,5,24) and crystallographic structure (25), elastase shares a high degree of sequence and functional homology with the zinc metalloprotease thermolysin of Bacillus thermoproteolyticus. These similarities to thermol-* Corresponding author.…”
mentioning
confidence: 99%
“…The sequence (1,6,31) and crystallographic structure (32) of elastase are known. It shares a high degree of sequence and functional homology with thermolysin, a zinc metalloprotease produced by Bacillus thermoproteolyticus.…”
mentioning
confidence: 99%